INFLUENCES OF SKILL DEVELOPMENT THROUGH SPECIFIC HANDBALL METHODS IN THE SECONDARY SCHOOL FOR THE SEVENTH GRADE - ANDREI Vivian; LEUCIUC Florin Valentin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In the game of handball the skill is a very important quality that facilitates proper assimilation of the technique and allows that the procedures and the technical and tactical actions to be easily executed in various game conditions and with increased efficiency. The purpose of the research is to determine by experiment the influence of the specific handball means in developing the driving quality - skill for seventh grade children. At the end of the study, following the results obtained we can see that there have been great advances for samples like: dribling between landmarks 30 m, throwing tennis balls, triangle movements. We believe that the facts presented in this paper and the research data highlight the important role of teaching handball in secondary schools and the role of deve